Stany nagłe w urologii - Salagierski, Maciej - red. nauk.; Jasiński, Miłosz; Nycz, Amanda; Megger, Katarzyna; Żabicki, Bartosz; Stroczyński, Maciej; Salagierski, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Urological emergencies: An overview for students and urology residents" is a comprehensive manual summarising urgent urological conditions with which urologists are confronted in clinical setting. The handbook includes chapters on emergent urological circumstances i.e. urosepsis, postrenal acute kidney injury, haematuria, urinary retention, urinary bladder tamponade, Fourier`s gangrene, testicular torsion, priapism, renal colic and trauma.
Keywords: urologia; stany nagłe; urosepsa; wodonercze; uraz; krwiomocz; priapizm; urology; emergencies; urosepsis; hydronephrosis; trauma; haematuria; priapism; podręcznik akademicki